Macroeconomic Fundamentals, Price Discovery and Volatility Dynamics in Emerging Markets. (IMF Working Papers; Working Paper ;, 2009)
This study characterizes volatility dynamics in external emerging bond markets and examines how prices and volatility respond to news about macroeconomic fundamentals. As in mature bond markets, macroeconomic surprises in external emerging bond markets are found to affect both conditional returns and volatility, with the effects on volatility being more pronounced and longer lasting than those on prices. Yet the process of information absorption tends to be more drawn out than in mature bond markets. International and regional macroeconomic news is at least as important as local news for both asset valuations and volatility dynamics in external emerging bond markets.